PERBAIKAN SISTEM PENGULIRAN PADA MESIN BUBUT DoALL LT 13 DI BENGKEL MEKANIK POLMAN BABEL - Yudha Pirmansyah, Sandika; Pratama , Jhasua; Ramli, Ramli; Pristiansyah, Pristiansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
The automatic threading system (half‑nut lever) on the DoALL LT‑13 lathe at Polman Babel's mechanical workshop failed to operate, disabling thread-cutting capability. This research aimed to document the repair process and post-repair functionality tests. The methods included 5 Why analysis, apron disassembly, cleaning, gear-idler clearance adjustment, gear surface lapping, and re-calibration of the half‑nut lever. Tests included functional check, dimensional accuracy, and thread cutting on three specimens: M27×3, M20×2.5, and M18×2.5. Results showed normal operation and all threads met ISO tolerance. The lathe is now functional for educational and light machining purposes.